Lipprint Patterns of Malay, Javanese, and Batak Tribes in Biology Education Students at Jambi University - Qurrota’Aini, Nasywa; Meilin, Meilin; Junia, Resy; Mulya, Yonata Wira; Siburian, Jodion; Anggereini, Evita; Saparuddin, Saparuddin; Tentia, Ine (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Lip printing (Cheiloscopy) is an effective secondary forensic identification method, based on the unique groove patterns in the lip mucosa that reflect genetic differences between ethnic groups. This descriptive cross-sectional study aimed to analyze and compare the lip print patterns of students from three main ethnic groups: Malay, Batak, and Javanese. A sample of 75 students (25 from each ethnic group) from the Biology Education Study Program, University of Jambi, was selected using a purposive sampling technique based on non-mixed criteria. Lip print analysis was performed visually and classified using the Suzuki-Tsuchihashi system which divides the patterns into six types (I, I’, II, III, IV, V). Lip print pattern Type I (Complete Vertical) was found to be the dominant pattern in all three ethnic groups, with the highest dominance in the Javanese (84.61%), followed by Malay (72%), and Batak (60%). Type V (Irregular) was not found in the sample. Contrary to previous studies, this study did not find significant variations in lip print patterns among the three ethnic groups. This Type I dominance may support the view that the three share a common ancestry or is caused by inter-ethnic interactions (gene flow) in a heterogeneous university environment. Therefore, there was no significant variation in lip print patterns between the Malay, Javanese, and Batak ethnic groups in this study population, with a consistent dominance of the Type I (complete vertical) pattern.